Selection of Contractors for a Housing Development Project in India by using an Integrated Model - Siva Sunku, Rajaprasad Venkata (International Journal of Sustainable Construction Engineering and Technology, 2018)
The Indian construction industry forms an integral part of the economy and a conduit for a substantial part of its development investment, is poised for growth on account of urbanization, economic development and peoples rising expectations for improved quality of living. Housing construction is usually executed or coordinated by contractors who specialize in one type of construction such as residential or commercial building. The completion of housing projects within the projected time span has always been the most challenging task for the construction organizations and it is found that many construction projects have been unsuccessful in delivering the projects at time, cost and quality which the clients and their consultants had perceived before the starting of the project and thus, it is important for the management to efficiently design a plan of action to achieve the goals and requirements. To accomplish the requirements of construction planning, identifying and selection of an appropriate contractor for housing development is a crucial decision making process. The study presented a method for solving a contractor selection problem in an Indian housing development project using combination of analytic hierarchy process and zeros one integer linear programming for allocating housing construction works to contractors. The proposed integrated model will provide an encouraging result to select a contractor for a particular type of housing construction to fulfil the quality requirements and completion of project on time.